LANGUAGE DEVELOPMENT IN A 1-YEAR-7-MONTH-OLD CHILD BASED ON PHONOLOGICAL AND SEMANTIC ASPECTS - Ningsih, Ningsih (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
he objective of this study is to analyze the language development of a 1-year-7-month-old child named Ary, with a focus on phonological and semantic aspects. The research was conducted through a three-month observation period, during which interactions between Ary and his surroundings, particularly his mother, were meticulously documented.The findings indicate that, in the phonological aspect, Ary has demonstrated the ability to produce various words, although there are pronunciation errors such as with the letters